Heterogeneous regional effects of rural credit on agricultural production in Brazil - Diogo Brito Sobreira; Francisco José Silva Tabosa; Edward Martins Costa; Ahmad Saeed Khan (Revista de Economia e Sociologia Rural, 2024)
Abstract Access to rural credit has been persistently heterogeneous across Brazilian regions over time. This work aimed to estimate the regional effects of rural credit on agricultural production due to the heterogeneity observed in access to credit. Based on data from the 2017 Agricultural Census and climate variables, the effect of rural credit was estimated by standard regressions, combined with the entropy balancing technique. The results show positive and significant effects of rural credit on Brazilian agricultural production, even after controlling for observed covariates. This result was consistent even after balancing the covariates with regard to entropy. The effect of rural credit proved to be heterogeneous across Brazilian regions, being positive and significant for regions with greater access to rural credit and statistically null in less credit-intensive regions. Furthermore, estimates show that technical assistance is an important transmission mechanism of the rural credit effect.